2015
DOI: 10.1001/jamaophthalmol.2015.44
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Cost-effectiveness of the Baerveldt Implant, Trabeculectomy With Mitomycin, and Medical Treatment

Abstract: IMPORTANCEThe Tube vs Trabeculectomy Trial (TVT) found that the 350-mm 2 Baerveldt implant (tube) and trabeculectomy with mitomycin may be similarly effective in lowering intraocular pressure in primary open-angle glaucoma. However, to date, there are no published long-term clinical data on the cost-effectiveness of trabeculectomy with mitomycin vs tube insertion.OBJECTIVE To assess the cost-effectiveness of these procedures compared with maximal medical treatment. DESIGN, SETTING, AND PARTICIPANTSWe used the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 46 publications
1
62
0
Order By: Relevance
“…MIGS have a favorable risk profile and appropriate effectiveness for a spectrum of glaucoma types either as an initial 4, 20, 21 , or as a secondary procedure 6 , and across a range of severity 22, 23 . This suggests that MIGS surgeons may play an increasing role in reducing the economic burden of glaucoma by providing an earlier and less expensive intervention 24, 25 than traditional glaucoma surgeries 26 .…”
Section: Introductionmentioning
confidence: 99%
“…MIGS have a favorable risk profile and appropriate effectiveness for a spectrum of glaucoma types either as an initial 4, 20, 21 , or as a secondary procedure 6 , and across a range of severity 22, 23 . This suggests that MIGS surgeons may play an increasing role in reducing the economic burden of glaucoma by providing an earlier and less expensive intervention 24, 25 than traditional glaucoma surgeries 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Cost is another important point. According to Kaplan et al, the mean costs for trabeculectomy, and tube insertion were $7872 and $10075, respectively with a cost difference of $2203 (95% CI, $2121-$2261) [17].…”
Section: Resultsmentioning
confidence: 99%
“…In such cases, the changes in cost effectiveness can be simulated using a probabilistic sensitivity analysis. In the study by Kaplan et al,22 the authors concluded that trabeculectomy was more likely to be preferred at lower WTP values.…”
Section: What Is the Magnitude Of The Treatment Effect?156mentioning
confidence: 99%
“…Kaplan et al22 assessed the cost effectiveness of trabeculectomy with MMC and Baerveldt implant and compared them with the maximal medical treatment according to the results of the TVT Study. The mean costs for medical treatment, trabeculectomy, and Baerveldt implantation were US $6172, US $7872, and US $10,075, respectively.…”
Section: What Is the Magnitude Of The Treatment Effect?156mentioning
confidence: 99%